Composition for foam molding, foam molded body, foamed electric wire, method for manufacturing foam molded body, method for manufacturing electric wire, and on-vehicle network cable

The foam molding composition, combining fluororesin and a specific compound with high pyrolysis temperature and solubility parameter, addresses the challenge of achieving efficient foaming and maintaining high-temperature properties in electric wires for on-vehicle network cables, resulting in improved surface smoothness and reduced sparks.

JP2025066145APending Publication Date: 2025-04-22DAIKIN INDUSTRIES LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2025012107
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-12-20
Filing Date
2025-01-28
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Existing electric wires for on-vehicle network cables do not adequately combine the physical properties of fluororesins with the benefits of foaming, particularly in terms of high temperature processing and efficient foaming without using fluorine surfactants.

Method used

A foam molding composition comprising a fluororesin (A) and a compound (B) with a pyrolysis temperature of 300° C. or higher and a solubility parameter (SP value) of 8 to 15, which is used to coat electrical wires for on-vehicle network cables, achieving excellent foaming properties and maintaining properties at high molding temperatures.

Benefits of technology

The composition achieves good foaming properties and maintains excellent physical properties even at high temperatures, resulting in a foamed wire suitable for on-vehicle network cables with improved surface smoothness and reduced spark occurrence.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025066145000001
    Figure 2025066145000001
  • Figure 2025066145000002
    Figure 2025066145000002
  • Figure 2025066145000003
    Figure 2025066145000003
Patent Text Reader

Abstract

To provide a foam molded body and a foamed electric wire which are suitably usable as an electric wire for an on-vehicle network cable.SOLUTION: A composition for foam molding contains a fluororesin (A) and a compound (B) having a thermal decomposition temperature of 300°C or higher and a solubility parameter (SP value) of 8 to 15, and is used for coating an electric wire for an on-vehicle network cable.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a foam molding composition, a foam molded product, a foam electric wire, a method for producing a foam molded product, a method for producing an electric wire, and an in-vehicle network cable. [Background technology]

[0002] Communication networks have become widespread in offices, homes, etc., but in recent years, with the increase in communication data volume accompanying the adoption of autonomous driving assistance systems, there is a demand for faster communication speeds in vehicles as well, and the introduction of network cables capable of high-speed communication, such as Ethernet (registered trademark), is progressing.

[0003] Patent Document 1 describes a shielded twisted pair cable having a twisted pair wire formed by twisting together a pair of core wires and a drain wire, each having an insulating coating around a signal conductor, a conductor foil covering the outer periphery of the twisted pair wire, and an outer insulating layer covering the outer periphery of the conductor foil, wherein the twisted pair wire is formed by twisting together at least two or more drain wires.

[0004] Patent Document 2 discloses an electric wire for an in-vehicle network cable that is covered with a fluororesin. Patent Document 3 discloses a foam molding composition and a foam electric wire using a fluororesin. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent Publication No. 2008-287948 [Patent Document 2] Patent Publication No. 2021-158111 [Patent Document 3] Patent Publication No. 2022-28640 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present disclosure is to provide a foam molded article and a foam electric wire that can be suitably used as an electric wire for an in-vehicle network cable. [Means for solving the problem]

[0007] The present disclosure relates to a foam molding composition comprising a fluororesin (A) and a compound (B) having a thermal decomposition temperature of 300°C or higher and a solubility parameter (SP value) of 8 to 15, the composition being used for covering an electric wire for an in-vehicle network cable.

[0008] The compound (B) is preferably a compound containing at least one partial structure selected from the group consisting of an aromatic ring, a phosphate ester group, and an amide group. The above compound (B) is preferably a compound containing one or more C6-14 aromatic rings or a salt thereof. The compound (B) is preferably at least one compound selected from the group consisting of phosphoric esters and their salts, phosphoric ester complex compounds, and compounds having two or more amide groups. The salt of compound (B) is preferably an alkali metal or alkaline earth metal salt.

[0009] The compound (B) is preferably at least one of the compounds represented by the following formulas (1), (2), (3) and (4). [ka] [ka] [ka] [ka] (In the formula, R1, R2, R3, R4, R 21 , R 22 , R 23 , R24 , R 31 , R 32 , R 33 , R 34 , R 41 , R 42 represents a hydrogen atom, an alkyl group or a cycloalkyl group having 1 to 8 carbon atoms, or an aryl group, an alkylaryl group, or an arylalkyl group having 6 to 12 carbon atoms; Ar41 represents an aryl group; R5 and R6 represent a hydrogen atom or a methyl group; n represents an integer of 1 or 2; m represents an integer of 0 to 2; and X represents a metal having a valence of m+n.

[0010] R1, R2, and R in formula (1), formula (2), and formula (3) 21 , R 22 , R 31 and R 33 is preferably an alkyl group having 1 to 8 carbon atoms. X in the formulas (1), (2) and (3) is preferably at least one of sodium, potassium, rubidium, calcium and barium.

[0011] The compound (B) is preferably an aromatic cyclic phosphate salt represented by the above formula (1). The compound (B) is preferably sodium 2,2'-methylenebis(4,6-di-t-butylphenyl)phosphate.

[0012] The above fluororesin (A) is preferably a melt-processable fluororesin. The fluororesin (A) is preferably at least one selected from the group consisting of tetrafluoroethylene / hexafluoropropylene copolymers, tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers, and tetrafluoroethylene / ethylene copolymers.

[0013] The fluororesin (A) is preferably a fluororesin that has been fluorination-treated. The foam molding composition of the present disclosure preferably contains substantially no fluorine-based low molecular weight compounds. The present disclosure also relates to a foam molded article obtained from the foam molding composition described above. It is preferable that the foamed molded article does not substantially contain a fluorine-based low molecular weight compound.

[0014] The present disclosure also provides a foamed electric wire for an in-vehicle network cable, comprising a core wire and a covering material obtained from the foam molding composition and covering the core wire. The foamed electric wire is preferably substantially free of fluorine-based low molecular weight compounds.

[0015] The present disclosure provides a wire having a core wire and a fluororesin layer or a fluororesin composition layer coated on the core wire, The fluororesin layer or the fluororesin composition layer is a foamed electric wire having bubbles, The foamed electric wire for an in-vehicle network cable is also characterized in that, in a cross section observation perpendicular to the length direction, the average bubble diameter of the bubbles is 20 to 40 μm.

[0016] The present disclosure also relates to a foamed electric wire for an in-vehicle network cable, comprising a core wire and a fluororesin layer or a fluororesin composition layer covering the core wire, the fluororesin layer or the fluororesin composition layer having bubbles, the bubbles having an average aspect ratio of 1.9 or less when observed in a cross section parallel to the longitudinal direction.

[0017] The present disclosure also relates to a foamed electric wire for an in-vehicle network cable, comprising a core wire and a fluororesin layer or a fluororesin composition layer covering the core wire, the fluororesin layer or the fluororesin composition layer having bubbles, wherein, when observed through a cross section parallel to the length direction, the proportion of bubbles having an aspect ratio of 3 or more is 13% or less of the total amount of bubbles measured when observed through a cross section parallel to the length direction.

[0018] The present disclosure also relates to a foamed electric wire for an in-vehicle network cable, comprising a core wire and a fluororesin layer or a fluororesin composition layer covering the core wire, the fluororesin layer or the fluororesin composition layer having bubbles, wherein, when observed from a cross section parallel to the longitudinal direction, the standard deviation of the aspect ratio of the bubbles is 1.3 or less.

[0019] The present disclosure also relates to a foamed electric wire for an in-vehicle network cable, comprising a core wire and a fluororesin layer or a fluororesin composition layer covering the core wire, the fluororesin layer or the fluororesin composition layer having bubbles, the foamed electric wire having an expansion rate of 20% or more and a surface roughness of less than 5.0 μm.

[0020] The present disclosure provides a wire having a core wire and a fluororesin layer or a fluororesin composition layer coated on the core wire, The fluororesin layer or the fluororesin composition layer is a foamed electric wire having bubbles, A foamed electric wire for in-vehicle network cables, characterized by a foam (inner) / skin (outer) structure.

[0021] The present disclosure also relates to a method for producing a foam molded article, comprising the step of foam molding the foam molding composition. The present disclosure also relates to a method for producing an electric wire, comprising the step of covering a core wire with the foam molding composition to obtain an electric wire.

[0022] The present disclosure also relates to an in-vehicle network cable including the foamed electric wire for the in-vehicle network cable. It is preferable that the in-vehicle network cable includes a twisted pair cable having a pair of electric wires twisted together, and at least one of the pair of electric wires is a foamed electric wire for the in-vehicle network cable. In the above-mentioned in-vehicle network cable, it is preferable that the deformation rate of the foamed electric wires in the twisted pair cable after twisting is 20% or less. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] The present disclosure has been completed based on the discovery that good foaming can be obtained by using a specific compound (B) in a foamable resin having a fluoropolymer as a base resin, and that this can be suitably used in particular for electric wires for in-vehicle network cables. The compound (B) has a thermal decomposition temperature of 300° C. or higher and a solubility parameter (SP value) of 8 to 15. Many conventional foam nucleating agents have relatively low thermal decomposition temperatures and melting points. This is not a problem when the molding temperature of the resin is low, but in molding compositions containing resins with high melting points, there is a problem that the agent is thermally decomposed or melted during the molding process and does not function efficiently as a foam nucleating agent. In particular, when a fluororesin, which is a high melting point resin, is used, inconveniences such as coloring, generation of decomposition gas, enlargement of the bubble size, deterioration of the surface condition, and deterioration of the electrical properties occur, making it difficult to achieve both the physical properties of the fluororesin and the properties of the foam molded product. The present disclosure has discovered that the use of compound (B) allows a composition containing fluororesin (A) to exhibit good foaming properties, and furthermore, allows the composition to exhibit good properties even when molded at high temperatures, thereby achieving the above-mentioned effects. The present disclosure will be described in detail below.

[0024] The fluororesin (A) is not particularly limited as long as it is melt-processable, and examples thereof include tetrafluoroethylene (TFE) / hexafluoropropylene (HFP) copolymers, TFE / perfluoro(alkyl vinyl ether) (PAVE) copolymers, TFE / ethylene copolymers (ETFE), chlorotrifluoroethylene (CTFE) / ethylene copolymers (ECTFE), polyvinylidene fluoride (PVdF), polychlorotrifluoroethylene (PCTFE), TFE / vinylidene fluoride (VdF) copolymers (VT), polyvinyl fluoride (PVF), TFE / VdF / CTFE copolymers (VTC), TFE / ethylene / HFP copolymers, and TFE / HFP / VdF copolymers.

[0025] Examples of the PAVE include perfluoro(methyl vinyl ether) [PMVE], perfluoro(ethyl vinyl ether) [PEVE], and perfluoro(propyl vinyl ether) [PPVE]. Among them, PPVE is preferable. These can be used alone or in combination.

[0026] The fluororesin may have polymerization units based on other monomers in an amount that does not impair the essential properties of each fluororesin. The other monomers can be appropriately selected from, for example, TFE, HFP, ethylene, propylene, perfluoro(alkyl vinyl ether), perfluoroalkyl ethylene, hydrofluoroolefin, fluoroalkyl ethylene, perfluoro(alkyl allyl ether), etc. The perfluoroalkyl group constituting the other monomers is preferably one having 1 to 10 carbon atoms.

[0027] The fluororesin is preferably a TFE / HFP copolymer, a TFE / PAVE copolymer, or a TFE / ethylene copolymer, because of its excellent heat resistance, and more preferably a TFE / HFP copolymer or a TFE / PAVE copolymer. The above fluororesins may be used in combination of two or more kinds. Perfluororesins are also preferred because of their superior electrical properties.

[0028] The TFE / HFP copolymer preferably has a TFE / HFP mass ratio of 80-97 / 3-20, and more preferably 84-92 / 8-16. The TFE / HFP copolymer may be a binary copolymer made of TFE and HFP, or may be a ternary copolymer made of TFE and a comonomer copolymerizable with HFP (for example, a TFE / HFP / PAVE copolymer). The TFE / HFP copolymer is also preferably a TFE / HFP / PAVE copolymer containing polymerized units based on PAVE. The TFE / HFP / PAVE copolymer preferably has a mass ratio of TFE / HFP / PAVE of 70-97 / 3-20 / 0.1-10, and more preferably 81-92 / 5-16 / 0.3-5.

[0029] The TFE / PAVE copolymer preferably has a mass ratio of TFE / PAVE of 90-99 / 1-10, and more preferably 92-97 / 3-8.

[0030] The TFE / ethylene copolymer preferably has a molar ratio of TFE / ethylene of 20 to 80 / 20 to 80, more preferably 40 to 65 / 35 to 60. The TFE / ethylene copolymer may contain other monomer components. That is, the TFE / ethylene copolymer may be a binary copolymer consisting of TFE and ethylene, or may be a ternary copolymer consisting of TFE and a comonomer copolymerizable with ethylene (for example, a TFE / ethylene / HFP copolymer). The TFE / ethylene copolymer is also preferably a TFE / ethylene / HFP copolymer containing polymerization units based on HFP. The TFE / ethylene / HFP copolymer preferably has a TFE / ethylene / HFP molar ratio of 40-65 / 30-60 / 0.5-20, more preferably 40-65 / 30-60 / 0.5-10.

[0031] The melt flow rate (MFR) of the fluororesin is preferably 0.1 to 500 g / 10 min, more preferably 4 to 100 g / 10 min, still more preferably 10 to 80 g / 10 min, and even more preferably 34 to 50 g / 10 min, particularly preferably 35 to 40 g / 10 min, since this can suppress the generation of sparks and increases the foaming rate. The MFR is a value measured in accordance with ASTM D-1238 using a die having a diameter of 2.1 mm and a length of 8 mm under a load of 5 kg at 372°C.

[0032] The fluororesin can be synthesized by polymerizing the monomer components using a conventional polymerization method, such as emulsion polymerization, suspension polymerization, solution polymerization, bulk polymerization, gas phase polymerization, etc. In the polymerization reaction, a chain transfer agent such as methanol may be used. The fluororesin may be produced by polymerization and isolation without using a metal ion-containing reagent.

[0033] The fluororesin may have terminal groups such as -CF3, -CF2H, etc., at least on one of the sites of the polymer main chain and the polymer side chain, and is not particularly limited, but is preferably a fluorination-treated fluororesin. A fluororesin that has not been fluorination-treated may have thermally and electrically unstable terminal groups such as -COOH, -CH2OH, -COF, -CONH2, etc. (hereinafter, such terminal groups are also referred to as "unstable terminal groups"). Such unstable terminal groups can be reduced by the fluorination treatment. It is preferable that the fluororesin contains few or no unstable terminal groups, and the total number of the four types of unstable terminal groups and the -CF2H terminal groups is less than 1×10 carbon atoms. 6 More preferably, the number of unstable terminal groups is 50 or less per unit. If the number exceeds 50, molding defects may occur. More preferably, the number of unstable terminal groups is 20 or less, and even more preferably, 10 or less. In this specification, the number of unstable terminal groups is a value obtained by infrared absorption spectrum measurement. The unstable terminal groups and -CF2H terminal groups may not exist, and all of the terminal groups may be -CF3 terminal groups.

[0034] The fluorination treatment can be carried out by contacting a non-fluorination-treated fluororesin with a fluorine-containing compound. The fluorine-containing compound is not particularly limited, and may be a fluorine radical source that generates fluorine radicals under fluorination treatment conditions, such as F2 gas, CoF3, AgF2, UF6, OF2, N2F2, CF3OF, and halogen fluorides (e.g., IF5, ClF3). The fluorine radical source such as F2 gas may be of 100% concentration, but from the viewpoint of safety, it is preferable to mix it with an inert gas and dilute it to 5 to 50 mass%, preferably 15 to 30 mass% before use. Examples of the inert gas include nitrogen gas, helium gas, and argon gas, and nitrogen gas is preferable from the viewpoint of economy. The conditions for the fluorination treatment are not particularly limited, and the fluorine-containing compound may be contacted with the molten fluororesin, but the treatment is usually carried out at a temperature below the melting point of the fluororesin, preferably at 20 to 220° C., and more preferably at 100 to 200° C. The fluorination treatment is generally carried out for 1 to 30 hours, and preferably for 5 to 20 hours. The above fluorination treatment is preferably one in which a non-fluorination-treated fluororesin is brought into contact with fluorine gas (F2 gas).

[0035] The fluororesin (A) is not particularly limited, but since a foamed molded product having excellent heat resistance and a wide continuous use temperature range can be obtained, it is desirable that the melting point is 200°C or higher, the molding temperature is 250°C or higher, and the thermal decomposition temperature is 300°C or higher. Furthermore, the melting point is more preferably 250°C or higher, and preferably 300°C or lower. The molding temperature is more preferably 300°C or higher, and preferably 450°C or lower. The thermal decomposition temperature is more preferably 350°C or higher, and even more preferably 400°C or higher. The upper limits of the melting point, molding temperature, and thermal decomposition temperature are 600°C or lower. In this specification, the melting point is the temperature measured by a differential scanning calorimeter (DSC), the molding temperature is a temperature generally recommended for molding, at which the resin has fluidity and does not deteriorate, such as coloring, and the thermal decomposition temperature is the temperature at which the resin loses 1% weight when heated in air at 10°C / min as measured by TG (thermal weight change measurement). However, this does not include the weight loss due to the volatilization of water contained in the resin or water of crystallization seen between 100°C and 200°C. Having fluidity means that the MFR is 0.0001 or more at the temperature.

[0036] In order to reduce signal loss in the communication cable, the dielectric constant of the fluororesin (A) is preferably 3.0 or less, more preferably 2.6 or less, and most preferably 2.1 or less. The lower limit is 1.0 or more. Similarly, the dielectric loss tangent is preferably 0.01 or less, more preferably 0.001 or less, and most preferably 0.0004 or less. The lower limit is 0.0001 or more. The dielectric constant and dielectric loss tangent are measured by a hollow resonator method at a frequency of 6 GHz.

[0037] The content of the fluororesin (A) is preferably 50 parts by mass or more, more preferably 80 parts by mass or more, still more preferably 90 parts by mass or more, even more preferably 95 parts by mass or more, and particularly preferably 98 parts by mass or more, relative to 100 parts by mass of the foam molding composition. The upper limit is 99.999 parts by mass or less, more preferably 99.99 parts by mass or less.

[0038] In the present disclosure, the compound (B) that acts as a foam nucleating agent is a compound having a thermal decomposition temperature of 300° C. or higher and a solubility parameter (SP value) of 8-15. In the present disclosure, in order to obtain a foamed molded article having excellent heat resistance and a wide continuous use temperature range, it is necessary that the thermal decomposition temperature of the compound (B) is 300° C. or higher. The thermal decomposition temperature is more preferably 350° C. or higher, and even more preferably 400° C. or higher. The upper limit is preferably 600° C. or lower. The thermal decomposition temperature can be measured in the same manner as for the above-mentioned fluororesin (A).

[0039] In order to effectively exert the effects of the present disclosure, it is desirable that the compound (B) is not melted at the molding temperature. Therefore, the melting point of the compound (B) is preferably 200°C or higher, more preferably 300°C or higher, more preferably 350°C or higher, and most preferably 400°C or higher. The melting point of the compound (B) is a temperature that can be confirmed by the TGA peak during TG measurement, and for example, when no peak is confirmed below 400°C, it is considered to be 400°C or higher. Whether or not the compound melts at the peak temperature is confirmed by using a heating microscope or an electric furnace in combination.

[0040] The compound (B) has a solubility parameter (SP value) of 8 to 15. When the SP value is within the above range, the additive particles can be uniformly dispersed and uniform and fine foaming can be achieved. Furthermore, the generation of giant particles due to particle re-agglomeration during foaming can be suppressed, and the unevenness of the electric wire surface caused by the giant particles can be reduced, resulting in a smooth surface. The SP value is preferably 9 or more, and more preferably 10 or more. Also, the SP value is preferably 14 or less, more preferably 13 or less, and even more preferably 12 or less. The above SP value can be determined by Fedors' formula (Polym. Eng. Sci., 14[2], 147 (1974)).

[0041] The compound (B) is preferably a compound containing at least one partial structure selected from the group consisting of an aromatic ring, a phosphate ester group, and an amide group. For example, when the compound (B) contains an aromatic ring, it is preferably a compound containing one or more C6-14 aromatic rings or a salt thereof.

[0042] When the compound (B) contains an amide group, it is preferable that the compound (B) has two or more amide groups. Such a compound is not particularly limited, and is preferably, for example, a compound represented by the following formula (4).

[0043] [ka]

[0044] (In the formula, R 41 , R 42 represents a hydrogen atom, an alkyl group or a cycloalkyl group having 1 to 8 carbon atoms, or an aryl group, an alkylaryl group, or an arylalkyl group having 6 to 12 carbon atoms; Ar 41 represents an aryl group.

[0045] More specifically, N,N'-dicyclohexyl-2,6-naphthalenedicarboxamide (trade name: NJSTAR NU-100, New Japan Chemical Co., Ltd.) can be mentioned.

[0046] When the compound (B) contains a phosphate group, it is preferably at least one compound selected from the group consisting of phosphates and their salts, and phosphate complex compounds. The phosphate compounds that can be used as the compound (B) are typically phosphates, phosphites, acid phosphates, acid phosphites, or salts thereof with ammonia, amines, melamine, alkali metals, alkaline earth metals, or the like, and the specific structure is not particularly limited.

[0047] Specific examples thereof include triphenyl phosphate, trilauryl phosphate, tristearyl phosphate, trioleyl phosphate, xylylene diphenyl phosphate, ethyl diphenyl phosphate, isopropyl diphenyl phosphate, n-butyl diphenyl phosphate, 2-ethylhexyl diphenyl phosphate, isodecyl diphenyl phosphate, cetyl diphenyl phosphate, stearyl diphenyl phosphate, oleyl diphenyl phosphate, butyl dicresyl phosphate, octyl dicresyl phosphate, lauryl dicresyl phosphate, dibutyl pyrophosphate, monophenyl acid phosphate, diphenyl acid phosphate, monocresyl acid phosphate, dicresyl acid phosphate, and monoxylenyl acid phosphate. phosphate, 2-acryloyloxyethyl acid phosphate, 2-methacryloyloxyethyl acid phosphate, diphenyl(2-acryloyloxyethyl)phosphate, diphenyl(2-methacryloyloxyethyl)phosphate, trinaphthyl phosphate, trinonylphenyl phosphate, tris(2,6-dimethylphenyl)phosphate, tetraphenylresorcinol diphosphate, tetraphenylhydroquinone diphosphate, tetraphenylbisphenol A diphosphate, tetra(2,6-dimethylphenyl)resorcinol diphosphate, tetra(2,6-dimethylphenyl)bisphenol A diphosphate, tetra(2,6-dimethylphenyl)biphenyl diphosphate, tetraphenylethylene glycol diphosphate, bis(2,Examples of the acidic phosphoric acid esters include 6-dimethylphenyl)pentaerythritol diphosphate, dixylenyl acid phosphate, and other acidic phosphoric acid esters, acidic phosphorous acid esters, dimethyl phosphate ammonium salt, diethyl phosphate ammonium salt, ethyl phosphate ammonium salt, di-n-butyl phosphate ammonium salt, dibutoxyethyl phosphate triethanolamine salt, dioctyl phosphate morpholine salt, mono-n-butyl phosphate soda salt, diphenyl phosphate ammonium salt, diphenyl phosphate melamine salt, diphenyl phosphate piperazine salt, phenyl phosphate ammonium salt, dicresyl phosphate ethylenediamine salt, cresyl phosphate soda salt, and dixylenyl phosphate melamine salt, and other acidic phosphoric acid esters, and acidic phosphorous acid esters, and salts of ammonia, amines, melamine, alkali metals, or alkaline earth metals.

[0048] More specific examples include salts of phosphate esters such as sodium bis(4-t-butylphenyl)phosphate and sodium 2,2'-methylenebis(4,6-di-t-butylphenyl)phosphate, (2-hydroxy-2-oxo-4,6,10,12-tetra-t-butyl-1,3,2-dibenzo[d,g]perhydrodioxaphosphalocin sodium salt, bisphenol phosphate diester barium salt, binaphthyl phosphate diester sodium salt, and bis(4-nitrophenyl)phosphate sodium. The ester may be a monoester, a diester, a triester, or an ester of more than one type. These may be used alone or in combination of two or more types.

[0049] Among them, aromatic phosphates are preferred, aromatic phosphate salts are more preferred, and aromatic phosphate salts having a cyclic structure are even more preferred. More preferred are cyclic phosphate salts having a biphenyl structure, a binaphthyl structure, or a benzohydryl structure, although the benzene ring or naphthalene ring may have an alkyl group or cycloalkyl group having 1 to 8 carbon atoms, or an aryl group, an alkylaryl group, or an arylalkyl group having 6 to 12 carbon atoms. The aromatic phosphate salt having a cyclic structure is preferably at least one of aromatic cyclic phosphate salts represented by the following formulas (1), (2) and (3).

[0050] [ka] [ka] [ka]

[0051] In the formula, R1, R2, R3, R 4、 R 21 , R 22 , R 23 , R 24 , R 31 , R 32 , R 33 , R 34 represents a hydrogen atom, an alkyl group or a cycloalkyl group having 1 to 8 carbon atoms, or an aryl group, an alkylaryl group, or an arylalkyl group having 6 to 12 carbon atoms; R 5 , R 6 represents a hydrogen atom or a methyl group, n represents an integer of 1 or 2, m represents an integer of 0 to 2, and X represents a metal having a valence of m+n.

[0052] R1, R2, R3, R 4、 R 21 , R 22 , R 23 , R 24 , R 31 , R32 , R 33 , R 34 Examples of the alkyl group represented by the formula (I) include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, amyl, isoamyl, sec-amyl, tert-amyl, hexyl, isohexyl, heptyl, octyl, isooctyl, 2-ethylhexyl, and tert-octyl. Examples of the cycloalkyl group include cyclopentyl, cyclohexyl, and cycloheptyl. Among these, alkyl groups having 1 to 4 carbon atoms and t-butyl groups are preferred.

[0053] R1, R2, R3, R 4、 R 21 , R 22 , R 23 , R 24 , R 31 , R 32 , R 33 , R 34 Examples of the aryl group represented by the formula (I) include phenyl, naphthyl, biphenyl, etc. Examples of the alkylaryl group include 4-methylphenyl, 4-tert-butylphenyl, nonylphenyl, etc. Examples of the arylalkyl group include benzyl, phenethyl, cumyl, etc.

[0054] Examples of the metal represented by X include alkali metals such as lithium, sodium, potassium, and rubidium, alkaline earth metals such as magnesium, calcium, and barium, aluminum, zinc, titanium, etc. Among these, at least one of sodium, potassium, rubidium, calcium, and barium is preferred, and sodium or barium is more preferred.

[0055] Among them, compound (B) is preferably an aromatic cyclic phosphate ester salt represented by the above formula (1), and more specifically, it is most preferably sodium 2,2'-methylenebis(4,6-di-t-butylphenyl)phosphate represented by the following formula (5).

[0056] [ka]

[0057] The phosphate complex compound that can be used as the compound (B) is a complex consisting of a metal and an organic compound having a phosphate, and the specific structure thereof is not particularly limited. Examples of the organic compound that constitutes this complex compound include bis(4,4',6,6'-tetra-t-butyl-2,2'-methylenediphenylphosphate, 2,2'-methylene-bis(4,6-di-t-butylphenyl)phosphate, 2,2'-methylene-bis(4,6-di-methylphenyl)phosphate, 2,2'-methylene-bis(4,6-di-methylphenyl)phosphate, 2,2'-methylene-bis(4,6-di-ethylphenyl)phosphate, 2,2'-methylene-bis(4-methyl ... 2,2'-ethyl-6-t-butylphenyl) phosphate, 2,2'-methylene-bis(4-ethyl-6-t-butylphenyl) phosphate, 2,2'-ethylidene-bis(4,6-di-t-butylphenyl) phosphate, 2,2'-ethylidene-bis(4-i-propyl-6-t-butylphenyl) phosphate, 2,2'-ethylidene-bis(4-m-butyl-6-t-butylphenyl) phosphate, 2,2'-butylidene-bis(4,6-di-methylphenyl) phosphate, 2,2'-butylidene -Bis(4,6-di-t-butylphenyl)phosphate, 2,2'-t-octylmethylene-bis(4,6-di-methylphenyl)phosphate, 2,2'-t-octylmethylene-bis(4,6-di-t-butylphenyl)phosphate, bis[2,2'-thiobis(4-ethyl-6-t-butylphenyl)phosphate], bis[2,2'-thiobis-(4,6-di-t-butylphenyl)phosphate], bis[2,2'-thiobis-(4-t-octylphenyl)phosphate], bis[2 ,2'-methylene-bis(4,6-di-t-butylphenyl)phosphate], bis[2,2'-ethylidene-bis(4,6-di-t-butylphenyl)phosphate], bis[(4,4'-dimethyl-6,6'-di-t-butyl-2,2'-biphenyl)phosphate], (4,4'-dimethyl-5,6'-di-t-butyl-2,2'-biphenyl)phosphate, tris[2,2'-methylene-bis(4,6-di-t-butylphenyl)phosphate], tris[2,2'-ethylidene-bis(4,6-di-t-butylphenyl)phosphate], phenyl bis dodecyl phosphate, phenyl ethyl hydrogen phosphate, phenyl bis (3,5,5-trimethylhexyl) phosphate, ethyl diphenyl phosphate, 2-ethylhexyl di(tolyl) phosphate, diphenyl hydrogen phosphate, methylene diphenyl phosphate, bis (2-ethylhexyl) p-tolyl phosphate, tritolyl phosphate, bis (2-ethylhexyl) phenyl phosphate, di (nonyl) phenyl phosphate, phenyl methyl hydrogen phosphate, di (dodecyl) p-tolyl phosphate, p-tolyl bis (2,5,5-trimethylhexyl ) phosphate, 2-ethylhexyl diphenyl phosphate, tri(butoxyethyl) phosphate, trioctyl phosphate, tricresyl phosphate, cresyl diphenyl phosphate, diethyl chlorophosphate, diphenyl chlorophosphate, diethyl bromophosphate, diphenyl bromophosphate, dimethyl chlorophosphate, phenyl chlorophosphate, trimethyl phosphate, triethyl phosphate, trino-butyl phosphate, tridecyl phosphate, triphenyl phosphate, isopropyl triphenyl phosphate, isodecyl diphenyl phosphate, methylene diphenyl phosphate, and the like.

[0058] Examples of metals constituting the phosphate ester complex compound include aluminum, sodium, lithium, calcium, magnesium, and barium. These may be used alone or in combination of two or more. Among these, aromatic phosphate esters are preferred, cyclic aromatic phosphate esters are more preferred, and sodium complex compounds of aromatic cyclic phosphate esters are most preferred.

[0059] Of the above-mentioned compounds (B), a specific example of a compound having a melting point of 300° C. or higher is sodium 2,2'-methylenebis(4,6-di-t-butylphenyl)phosphate.

[0060] The content of the compound (B) relative to the fluororesin (A) is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, even more preferably 5 parts by mass or less, even more preferably 2 parts by mass or less, and particularly preferably 1.5 parts by mass or less. The content of the compound (B) is preferably 0.001 part by mass or more relative to the fluororesin (A), and more preferably 0.01 part by mass or more. If the content of compound (B) is too low, it becomes difficult to obtain fine bubbles in the resulting coating material, whereas if the content is too high, there is a risk of frequent sparks being generated.

[0061] The foam molding composition of the present disclosure may further contain boron nitride to the extent that the effects of the present disclosure are not impaired.

[0062] The boron nitride preferably has an average particle size of 8.0 μm or more. Conventionally, there has been a trend toward smaller average particle sizes of boron nitride, and the use of boron nitride with a relatively large average particle size has not been specifically considered. The foam molding composition of the present disclosure contains boron nitride having an average particle size in the above-mentioned specific range, making it possible to form a foamed electric wire having a covering material with a smaller average bubble size and a higher foaming rate.

[0063] The average particle size of the boron nitride is preferably 9.0 μm or more, more preferably 10.0 μm or more, even more preferably 10.5 μm or more, particularly preferably 11.0 μm or more, particularly more preferably 12.0 μm or more, and most preferably 13.0 μm or more. On the other hand, if the average particle size of boron nitride is too large, the average bubble size may become large and there may be a risk of frequent sparks being generated.The average particle size of boron nitride is preferably 25 μm or less, and more preferably 20 μm or less. When the average particle size of boron nitride is within the above range, a coating material having fine and uniform bubbles can be formed. The average particle size of boron nitride is a value determined using a laser diffraction / scattering particle size distribution analyzer. When using a wet method, the medium may be appropriately selected, for example, methanol or the like may be used.

[0064] The boron nitride preferably has a particle size distribution represented by (D84-D16) / D50 of 1.2 or less. D84, D50 and D16 represent the particle size (μm) at the point where the cumulative curve is 84%, 50% and 16% when the total volume of the boron nitride powder group is taken as 100%. The particle size distribution is accumulated from the small particle size side. The total volume of the powder group is obtained by preparing a sample by dispersing boron nitride powder in a medium such as methanol and using a laser diffraction / scattering particle size distribution analyzer (e.g., Microtrac MT3300 manufactured by Nikkiso Co., Ltd.). By having the particle size distribution of boron nitride fall within the above range, a coating material having fine and uniform bubbles can be formed, and the generation of sparks can be further suppressed. The particle size distribution is more preferably 1.1 or less, and even more preferably 1.0 or less. The lower limit of the particle size distribution is not particularly limited, but may be, for example, 0.1. The cumulative curve of the particle size distribution (volume particle size distribution) is obtained using a laser diffraction / scattering particle size distribution analyzer (e.g., Microtrack MT3300 manufactured by Nikkiso Co., Ltd.) When a wet method is used, the medium may be appropriately selected, and for example, methanol or the like may be used.

[0065] It is preferable that the boron nitride is pulverized. When the boron nitride is pulverized, the generation of sparks can be further suppressed. The above-mentioned pulverization can be carried out by a method and under conditions that allow the average particle size and particle size distribution of boron nitride to fall within the above-mentioned ranges. For example, the type and conditions of the pulverizer can be appropriately selected. As the pulverizer, for example, a jet mill, a hammer mill, a ball mill, a pin mill, etc. can be used.

[0066] The boron nitride may be classified to adjust the average particle size or particle size distribution within the above range. The composition of the present disclosure is not particularly limited, but for example, the content of boron nitride is preferably 0.1 to 10 mass%, more preferably 0.1 to 2.0 mass%, even more preferably 0.1 to 1.5 mass%, and even more preferably 0.1 to 1.0 mass%. If the content of boron nitride is too low, it may be difficult to obtain fine bubbles in the resulting foamed electric wire covering material, and if the content is too high, the production cost may increase.

[0067] The foam molding composition of the present disclosure may further contain a polyatomic anion-containing inorganic salt, provided the effects of the present disclosure are not impaired. Examples of the polyatomic anion-containing inorganic salts include those disclosed in US Pat. No. 4,764,538.

[0068] The foam molding composition of the present disclosure may further contain sulfonic acid, phosphonic acid, or salts thereof, zeolite, etc., within the scope not impairing the effects of the present disclosure. In addition, an organic foam nucleating agent such as ADCA (azodicarbonamide), DPT (N,N'-dinitropentamethylenetetramine), or OBSH (4,4'-oxybisbenzenesulfonylhydrazide) may be used in combination.

[0069] The foam molding composition of the present disclosure may contain, in addition to the fluororesin (A) and the compound (B), a conventionally known filler, provided the effect of the present disclosure is not impaired.

[0070] Examples of the filler include graphite, carbon fiber, coke, silica, zinc oxide, magnesium oxide, magnesium sulfate, tin oxide, antimony oxide, calcium carbonate, magnesium carbonate, magnesium hydroxide, glass, talc, mica, aluminum nitride, calcium phosphate, sericite, diatomaceous earth, silicon nitride, fine silica, fumed silica, alumina, zirconia, quartz powder, kaolin, bentonite, titanium oxide, etc. The shape of the filler is not particularly limited, and examples thereof include fibrous, needle-like, columnar, whisker-like, flat, layered, scaly, balloon-like, porous, chopped fiber, powder, granular, bead-like, etc. Note that the filler is different from boron nitride.

[0071] The foam molding composition of the present disclosure may further contain a thermoplastic resin other than the above-mentioned fluororesin. Examples of the thermoplastic resin other than the above-mentioned fluororesin include general-purpose resins such as polyethylene resin, polypropylene resin, vinyl chloride resin, and polystyrene resin; engineering plastics such as nylon, polycarbonate, polyetheretherketone resin, polyphenylene sulfide resin, polyaryletherketone (PAEK), polyetherketoneketone (PEKK), polyetherketone (PEK), polyetheretherketoneketone (PEEKK), etc., polyethersulfone (PES), liquid crystal polymer (LCP), polysulfone (PSF), amorphous polyarylate (PAR), polyethernitrile (PEN), thermoplastic polyimide (TPI), polyimide (PI), polyetherimide (PEI), and polyamideimide (PAI).

[0072] The foam molding composition of the present disclosure may further contain other components such as additives, etc. Examples of other components include fillers such as glass fiber, glass powder, asbestos fiber, cellulose fiber, and carbon fiber, as well as reinforcing agents, stabilizers, lubricants, pigments, flame retardants, and other additives. The foam molding composition of the present disclosure can also be obtained by a production method (hereinafter referred to as a "production method of the composition") that includes a mixing step of mixing the fluororesin (A), the compound (B), and boron nitride, a filler, additives, etc., which are added as necessary, to obtain a mixture.

[0073] The above mixing method may be, for example, a conventionally known method, but a mixing method which does not easily cause aggregation of the compound (B) is preferred. The above mixing method may include a method using a Henschel mixer, a ribbon mixer, a V blender, a ball mill, etc. Another example is a mixing method by melt kneading.

[0074] The method for producing the foam molding composition of the present disclosure may include a kneading step of kneading the mixture obtained by the mixing step. The kneading step can produce pellets. The kneading step can be carried out by a method using a conventional melt kneader such as a single screw extruder or a twin screw extruder.

[0075] The method for producing the foam molding composition may include a step of fluorinating the fluororesin. The fluorination treatment may be performed by the above-mentioned method. The fluorination treatment may be performed, for example, by contacting the pellets obtained by the above-mentioned kneading with the above-mentioned fluorine-containing compound.

[0076] The components already explained as being capable of being contained in the foam molding composition of the present disclosure, such as thermoplastic resins other than fluororesins, boron nitride, inorganic salts containing polyatomic anions, fillers, and other additives, can be added as appropriate in each step of the method for producing the foam molding composition, depending on their properties, etc. Furthermore, fluororesins and boron nitride may be further added.

[0077] The foam molding composition of the present disclosure can be suitably used as a foamable composition. Furthermore, the foam molding composition can be suitably used as a wire covering composition for forming a covering material for an electric wire.

[0078] The foam molding composition of the present disclosure exhibits good foaming properties without using a fluorine-based surfactant. Fluorine-based low molecular weight compounds have been widely used as conventional fluorine-based surfactants. If such low molecular weight compounds are contained in large amounts, there is a problem that the molten resin during molding is plasticized, resulting in an increase in sparks. Since the foam molding composition of the present disclosure does not substantially contain such low molecular weight compounds, it is possible to obtain a foam molded article with excellent surface condition without causing the above-mentioned problems.

[0079] The fluorine-based low molecular weight compound is not particularly limited, and examples thereof include perfluoroalkyl acids and perfluorosulfonic acids. Specifically, C8F 17 COOH and its salts, C7F 15 COOH and its salts, C6F 13 COOH and its salts, C8F 17 SO3H and its salts, C6F 13 SO3H and its salts, C4F9SO3H and its salts, C8F 17 CH2CH2-SO3H and its salts, C6F 13 CH2CH2-SO3H and its salts, C8F 17 CH2CH2OH, C6F 13 CH2CH2OH, and more specifically, {F(CF2)6CH2CH2SO3}2Ba.

[0080] The content of the above-mentioned fluorine-based low molecular weight compounds can be analyzed by the following method: The pellets of the foam molding composition were pulverized by freeze-pulverization, and the resulting powder was dispersed in methanol and extracted by applying ultrasonic waves at 60° C. for 2 hours. The content of the extract was determined by a liquid chromatograph-mass spectrometer (LC-MS / MS).

[0081] The method for producing a foam molded article of the present disclosure includes a step of foam molding the foam molding composition.

[0082] The method for foam-molding the foam molding composition is not particularly limited, and for example, a conventionally known method can be used, such as a method in which a gas is used for the molten fluororesin (molten resin), the foam molding composition of the present disclosure is fed into a screw extruder designed for foaming operations, and a continuous gas injection method is used.

[0083] The gas may be, for example, chlorodifluoromethane, nitrogen, carbon dioxide, or a mixture of the above gases, and may be introduced into the molten resin in the extruder as a pressurized gas or may be generated by mixing a chemical foaming agent into the molten resin. The gas dissolves in the molten resin in the extruder.

[0084] The gas dissolved in the molten resin escapes the melt due to the sudden drop in melt pressure as it exits the extrusion die. The extrudate leaving the extruder is then cooled and solidified, for example by immersion in water.

[0085] The foamed molded article is obtained by foaming the foam molding composition, and therefore has a low dielectric constant, exhibits stable capacitance, is lightweight, and can be obtained as a covering material described below with stable dimensions such as wire diameter and thickness. The total volume of bubbles in the foamed molded product can be appropriately adjusted according to the application, for example, by adjusting the amount of gas introduced into the extruder or by selecting the type of gas to be dissolved.

[0086] The foamed molded article is obtained as a molded article molded according to the application during extrusion from the extruder. The molding method is not particularly limited as long as it is hot melt molding, and examples thereof include extrusion foam molding, injection foam molding, and mold foam molding.

[0087] The shape of the foamed molded article is not particularly limited, and may be in various shapes, such as a covering material for foamed electric wires, a filament-like shape such as a wire, a sheet-like shape, a film-like shape, a rod-like shape, a pipe-like shape, etc. The foamed molded article can be used as, for example, an electrical insulating material, a heat insulating material, a sound insulating material, a lightweight structural material such as a floating material, a buffer material such as a cushion, etc. The foamed molded article can be particularly suitably used as a covering material for foamed electric wires. The obtained foamed molded article contains a molten solidified body of the foam-molding composition of the present disclosure and bubbles, and the bubbles are preferably uniformly distributed in the molten solidified body. The average bubble diameter of the bubbles is not limited, but is preferably, for example, 60 μm or less. The average bubble diameter is preferably 0.1 μm or more. The foaming ratio of the foamed molded product is preferably 20% or more, but is not particularly limited thereto. The upper limit of the foaming ratio is, for example, 80%, but is not particularly limited thereto.

[0088] One of the features of the foam molded article of the present disclosure is that the surface is smoother than that of conventional foam molded articles containing fluororesins. Because of the smooth surface, the foam molded article can be suitably used for twin-ax cables and the like. In the present disclosure, the surface of the foamed molded article can be evaluated by scanning it with a bare hand and observing the degree of catching (protrusion) felt by the hand. In addition, as described later, the surface of the electric wire can be measured with a laser microscope, and the obtained image data can be corrected by specifying the range of the electric wire by quadratic surface correction of surface shape correction, and then the surface roughness of 500 x 2000 μm can be calculated, so that the surface roughness can be evaluated numerically. The above surface roughness is preferably less than 10.0 μm, more preferably less than 7.0 μm, and even more preferably less than 5.0 μm. The lower limit of the surface roughness may be 0.001 μm or more. In the case of a twin-ax cable or the like, a two-layer structure of foam (inside) / skin (outside) is preferable because the surface roughness can be controlled to a more preferable value.

[0089] The method for producing an electric wire according to the present disclosure includes a step of obtaining an electric wire by covering a core wire with the foam molding composition. By using the foam molding composition, a foamed electric wire having a covering material having fine and uniform bubbles can be formed. The step of obtaining the electric wire preferably involves foam molding the foam molding composition. The electric wire obtained by the method for producing an electric wire comprises a core wire and a covering material formed from the foam molding composition. The electric wire obtained by covering a core wire with the foam molding composition also constitutes one aspect of the present disclosure.

[0090] The covering material is obtained by covering a core wire with the foam molding composition, and therefore has fine and uniform bubbles, a low dielectric constant, a stable capacitance, is lightweight, and can have a stable shape with respect to dimensions such as wire diameter and thickness. Moreover, the covering material has a smooth surface similar to the foamed molded article, and exhibits similar physical properties.

[0091] The electric wire can be produced by a conventional method, for example, by extrusion foam molding, except that the core wire is covered with the foam molding composition. Preferred extrusion conditions can be appropriately selected depending on the composition of the composition used and the size of the core wire.

[0092] Examples of the method for coating the core wire with the foam molding composition include a method in which a gas soluble in molten fluororesin (molten resin) is used, the foam molding composition of the present disclosure is fed into a screw extruder designed for foaming operations, and a continuous gas injection method is used. The gas used can be the same as that used in the production method of foam molded articles.

[0093] The resulting covering material contains a molten solidified product of the foam-molding composition of the present disclosure and gas bubbles, and it is preferable that the gas bubbles are uniformly distributed in the molten solidified product. The average bubble diameter of the bubbles is not limited, but in cross-sectional observation perpendicular to the length direction, it is preferably 200 μm or less, more preferably 100 μm or less, even more preferably 50 μm or less, even more preferably 40 μm or less, particularly preferably 30 μm or less, and especially preferably 20 μm or less. The average bubble diameter is preferably 0.1 μm or more, more preferably 0.5 μm or more, and more preferably 1 μm or more. However, in order to reduce the bubble diameter, it is necessary to add a large amount of additive, and if the amount is too large, sparks are likely to occur, so the average bubble diameter of the electric wire for in-vehicle network is preferably 20 to 40 μm, and particularly preferably 25 to 35 μm. Such a structure of the covering material is obtained due to the combination of the fluororesin (A) and the specific compound (B) in the foam molding composition of the present disclosure. The average bubble diameter is a value obtained by taking an image of the cross section of the coating material using a scanning electron microscope (SEM), calculating the diameter of each bubble by image processing, and averaging the calculated diameter.

[0094] The coating material preferably has an expansion rate of 20% or more, more preferably 25% or more, and even more preferably 30% or more. Particularly preferably, the expansion rate is 40% or more. There is no particular upper limit, but it is, for example, 90%. The upper limit of the expansion rate may be 80% or 60%. In the case of electric wires for in-vehicle networks, a range of 40% to 60% is preferable in consideration of crushing during twisting. The expansion ratio is a value calculated by ((specific gravity of fluororesin-specific gravity of foam) / specific gravity of fluororesin) x 100. The expansion ratio can be appropriately adjusted according to the application, for example, by adjusting the amount of gas introduced into the extruder or by selecting the type of gas to be dissolved.

[0095] The coating material preferably has less than 5 sparks per 3,500 m, more preferably less than 3 sparks, and even more preferably 1 spark or less. The above spark counts were measured using a Beta LaserMike Sparktester HFS1220 at a voltage of 1500V.

[0096] The core wire may be made of a metal conductive material such as copper or aluminum, or carbon, etc. The core wire may be made of a single material, or may have its surface plated with silver, tin, or the like. The core wire preferably has a diameter of 0.02 to 3 mm. The diameter of the core wire is more preferably 0.04 mm or more, further preferably 0.05 mm or more, and particularly preferably 0.1 mm or more. The diameter of the core wire is more preferably 2 mm or less. The core wire may be a solid wire or a stranded wire in which a plurality of core wires are stranded together. The shape of the core wire is not particularly limited, and examples thereof include a flat shape and a rectangular wire. The electric wire is preferably one in which the covering material has a thickness of 0.01 to 3.0 mm. It is also preferable that the covering material has a thickness of 2.0 mm or less. Specific examples of the core wire include AWG (American Wire Gauge)-46 (solid copper wire with a diameter of 40 micrometers), AWG-42 (solid copper wire with a diameter of 64 micrometers), AWG-36 (solid copper wire with a diameter of 127 micrometers, a wire with a total diameter of 153 micrometers made by twisting seven copper wires with a diameter of 51 micrometers), AWG-30 (solid copper wire with a diameter of 254 micrometers, a wire with a total diameter of 306 micrometers made by twisting seven copper wires with a diameter of 102 micrometers), AWG-27 ​​(solid copper wire with a diameter of 361 micrometers), AWG-26 (solid copper wire with a diameter of 404 micrometers), AWG-24 (solid copper wire with a diameter of 510 micrometers), and AWG-22 (solid copper wire with a diameter of 635 micrometers).

[0097] The foamed electric wire comprises a core wire and a covering material that covers the core wire. The foamed electric wire can be used as cables connecting computers and their peripheral devices, cables for communicating high-capacity video and audio at high speed, cables for connecting servers in a data center, for example, LAN cables, USB cables, Lightning cables, Thunderbolt cables, CATV cables, HDMI (registered trademark) cables, QSFP cables, aerospace electric wires, underground power transmission cables, submarine power cables, high-voltage cables, superconducting cables, wrapped electric wires, automotive electric wires, wire harnesses and electrical equipment, electric wires for robots and FA, electric wires for OA equipment, electric wires for information equipment (optical fiber cables, audio cables, etc.), internal wiring for communication base stations, internal wiring for large currents (inverters, power conditioners, storage battery systems, etc.), internal wiring for electronic devices, wiring for small electronic devices and mobile devices, wiring for moving parts, internal wiring for electrical equipment, internal wiring for measuring instruments, power cables (for construction, wind power / solar power generation, etc.), cables for control and instrumentation wiring, cables for motors, etc.

[0098] The electric wire may have a two-layer structure (skin-foam) in which a non-foamed layer is inserted between the core wire and the covering material, a two-layer structure (foam-skin) in which a non-foamed layer is covered on the outer layer, or even a three-layer structure (skin-foam-skin) in which a non-foamed layer is covered on the outer layer of skin-foam. To reduce the surface roughness, a foam-skin or skin-foam-skin structure is preferred. Foam-skin is preferred because it can simplify the equipment. The total thickness of the skin layer is preferably 200 μm or less, more preferably 100 μm or less, particularly preferably 70 μm or less, and most preferably 40 μm or less. Also, it is preferably 1 μm or more. The non-foamed layer of the electric wire is not particularly limited, and may be a resin layer made of a resin such as a TFE / HFP copolymer, a TFE / PAVE copolymer, a TFE / ethylene copolymer, a vinylidene fluoride polymer, a polyolefin resin such as polyethylene (PE), or a polyvinyl chloride (PVC).

[0099] Since the foam molding composition of the present disclosure is substantially free of fluorine-based low molecular weight compounds, the foam molded article and electric wire described above are also substantially free of fluorine-based low molecular weight compounds. The content of the fluorine-based low molecular weight compound in the foam-molded article and electric wire can be analyzed in the same manner as in the case of the foam-molding composition described above.

[0100] The present disclosure also relates to the foamed electric wires listed below. (1) A foamed electric wire comprising a core wire and a fluororesin layer or a fluororesin composition layer covering the core wire, the fluororesin layer or the fluororesin composition layer having bubbles, the bubbles having an average aspect ratio of 1.9 or less when observed in a cross section parallel to the longitudinal direction. (2) A foamed electric wire having a core wire and a fluororesin layer or a fluororesin composition layer covering the core wire, the fluororesin layer or the fluororesin composition layer having bubbles, wherein, when observed through a cross section parallel to the length direction, the proportion of bubbles having an aspect ratio of 3 or more is 13% or less of the total amount of bubbles measured through the cross section parallel to the length direction. (3) A foamed electric wire comprising a core wire and a fluororesin layer or a fluororesin composition layer covering the core wire, the fluororesin layer or the fluororesin composition layer having bubbles, wherein the standard deviation of the aspect ratio of the bubbles is 1.3 or less when observed on a cross section parallel to the longitudinal direction. (4) A foamed electric wire comprising a core wire and a fluororesin layer or a fluororesin composition layer covering the core wire, the fluororesin layer or the fluororesin composition layer having bubbles, the foamed electric wire having an expansion rate of 20% or more and a surface roughness of less than 5.0 μm. (5) A foamed electric wire comprising a core wire and a fluororesin layer or a fluororesin composition layer covering the core wire, the fluororesin layer or the fluororesin composition layer having bubbles, the bubbles having an average diameter of 20 to 40 μm when observed in a cross section perpendicular to the length direction. (6) A core wire and a fluororesin layer or a fluororesin composition layer coated on the core wire, The fluororesin layer or the fluororesin composition layer is a foamed electric wire having bubbles, A foamed electric wire for in-vehicle network cables, characterized by a foam (inner) / skin (outer) structure.

[0101] The fact that the bubbles contained in the fluororesin layer or fluororesin composition layer satisfy these physical properties indicates that the bubbles are fine and uniform, and it can be said that the dielectric constant is low and a stable capacitance is exhibited. These fluororesin layers and fluororesin composition layers can be formed, for example, from the foam-molding composition of the present disclosure.

[0102] The average aspect ratio of the bubbles is 1.9 or less. The average aspect ratio can be measured by taking an image of a cut surface parallel to the longitudinal direction of the coating material using a scanning electron microscope (SEM), and calculating the ratio of the major axis to the minor axis (major axis / minor axis) from the major axis and minor axis of each bubble obtained by image processing, and averaging the aspect ratios obtained. The average aspect ratio is preferably 1.8 or less, more preferably 1.6 or less. Also, it is preferably 1.0 or more.

[0103] The proportion of bubbles with an aspect ratio of 3 or more is 13% or less of the total amount of bubbles measured in a cross section parallel to the length direction. The proportion is calculated by taking an image of a cross section parallel to the length direction of the coating material with a scanning electron microscope (SEM), and calculating the ratio of the long diameter to the short diameter (long diameter / short diameter) from the long diameter and short diameter of each bubble obtained by image processing. The proportion of bubbles having an aspect ratio of 3 or more is preferably 6% or less, more preferably 3% or less, and more preferably 0.01% or more.

[0104] The standard deviation of the aspect ratio of the bubbles is 1.3 or less. The standard deviation is calculated by taking an image of a cut surface parallel to the length direction of the coating material using a scanning electron microscope (SEM) and calculating the ratio of the major axis to the minor axis (major axis / minor axis) from the major axis and minor axis of each bubble obtained by image processing. The standard deviation of the aspect ratio is preferably 1.1 or less, more preferably 0.8 or less, and more preferably 0.6 or less. Also, it is preferably 0.01 or more.

[0105] The expansion ratio is preferably 20% or more. The expansion ratio is a value calculated by ((specific gravity of fluororesin-specific gravity of fluororesin layer or fluororesin composition layer) / specific gravity of fluororesin)×100. The foaming ratio is more preferably 25% or more, more preferably 30% or more, and further preferably 40% or more.

[0106] The surface roughness is less than 5.0 μm. The surface roughness is measured by measuring the surface of the electric wire using a laser microscope manufactured by Keyence Corporation, correcting the image data obtained by specifying the area of ​​the electric wire using quadratic curve correction for surface shape correction, and then calculating the surface roughness of a 500 x 200 μm area. The surface roughness is most preferably 3.0 μm or less.

[0107] In observation of a cut surface perpendicular to the length direction, the average bubble diameter of the bubbles is 20 to 40 μm, preferably 25 to 35 μm. The average bubble diameter is a value obtained by taking an image of the cross section of the coating material using a scanning electron microscope (SEM), calculating the diameter of each bubble by image processing, and averaging the calculated diameters.

[0108] In the above-mentioned foamed electric wire, when a cross section perpendicular to the length direction is observed, the average bubble diameter of the bubbles is preferably 50 μm or less. The average bubble diameter is more preferably 40 μm or less, and even more preferably 35 μm or less. The average bubble diameter is preferably 0.1 μm or more, more preferably 20 μm or more, and even more preferably 25 μm or more.

[0109] Furthermore, it is preferable that 90% or more of the bubbles have an average bubble diameter of 50 μm or less, and more preferably 95% or more. The maximum bubble diameter is preferably 150 μm or less, and more preferably 100 μm or less. The number of bubbles in the cross section is 1500 / mm 2 Preferably less than 1000 pieces / mm 2 Less than 800 pieces / mm is more preferable. 2 The following is even more preferred:

[0110] In the above-mentioned foamed electric wire, the coating thickness of the fluororesin layer or fluororesin composition layer is preferably 0.4 mm or less, more preferably 0.3 mm or less, and even more preferably 0.25 mm or less. The coating thickness is calculated by (outer diameter of the electric wire coating-core diameter) / 2.

[0111] In the above-mentioned foamed electric wire, the core diameter is preferably 0.5 mm or less, more preferably 0.4 mm or less, and even more preferably 0.3 mm or less.

[0112] The above-mentioned foamed electric wire is not particularly limited in its manufacturing method, but is preferably manufactured by the manufacturing method of a foamed electric wire using the foam molding composition of the present disclosure. That is, by using the foam molding composition of the present disclosure, a foamed electric wire having the above-mentioned properties can be obtained, and various excellent properties can be obtained. The manufacturing method of the foamed electric wire of the present disclosure described above can be carried out by the steps described above.

[0113] The foam molding composition of the present disclosure is used for covering electric wires for in-vehicle network cables. The electric wire for an in-vehicle network cable can be suitably used for a wide range of vehicles, from large commercial vehicles to private cars.

[0114] The vehicle-mounted network cable of the present disclosure includes a twisted pair cable having a pair of electric wires twisted together, and at least one of the pair of electric wires is preferably a foamed electric wire for vehicle-mounted network cables of the present disclosure. In addition, from the viewpoint of maintaining electrical properties, it is preferable that the crushing of the twisted electric wires after twisting is small, and the deformation rate is preferably 20% or less.

[0115] The in-vehicle network cable of the present disclosure includes the foamed wire for the in-vehicle network cable of the present disclosure. The present disclosure also provides a use of the in-vehicle network cable for an in-vehicle network.

[0116] The in-vehicle network cable of the present disclosure may be in the form of a coaxial cable, a twisted pair cable, two parallel wires, four parallel wires, eight parallel wires, or the like.

[0117] The coaxial cable may be, for example, a cable in which an outer conductor layer (e.g., metal mesh or the like) made of metal is formed around the foamed electric wire for the in-vehicle network cable of the present disclosure, and a resin layer (sheath layer) is formed around the outer conductor layer. The resin layer (sheath layer) is not particularly limited, and may be a layer made of a resin such as a fluorine-containing copolymer having a TFE unit, such as a TFE / HFP copolymer or a TFE / PAVE copolymer, polyvinyl chloride (PVC), or polyethylene. The outer conductor layer and the resin layer (sheath layer) may be covered by a conventionally known method.

[0118] The vehicle-mounted network cable of the present disclosure includes a twisted pair cable having a pair of wires twisted together, and at least one of the pair of wires is preferably the foamed wire for vehicle-mounted network cable of the present disclosure. The use of a twisted pair cable makes it less susceptible to noise, and is particularly suitable as a vehicle-mounted network cable that is prone to generating large noise.

[0119] The in-vehicle network cable of the present disclosure may include one pair of twisted pair cables, or may include two or more pairs of twisted pair cables. The number of twisted pair cables is preferably 1 to 4, more preferably 1 or 2, and further preferably 1.

[0120] The vehicle-mounted network cable of the present disclosure preferably includes a jacket surrounding the twisted pair cable. Materials for the jacket include, but are not limited to, fluorine-containing copolymers having TFE units such as TFE / HFP copolymers and TFE / PAVE copolymers, polyvinyl chloride (PVC), polyethylene, and other resins. The thickness of the jacket is not particularly limited and may be appropriately set according to the purpose.

[0121] The vehicle-mounted network cable of the present disclosure may have an external conductor layer (e.g., metal mesh, aluminum foil, etc.) made of metal around the twisted pair cable. The external conductor layer functions as a shield, further improving stability. However, from the viewpoint of light weight and bendability, it is preferable not to have a shield.

[0122] The in-vehicle network cable of the present disclosure is preferably an in-vehicle Ethernet cable, and more specifically, is more preferably a 100BASE-T1 or 1000BASE-T1 network cable.

[0123] The present disclosure also provides an in-vehicle network system including an in-vehicle computer and an in-vehicle network cable of the present disclosure connected to the in-vehicle computer. The in-vehicle network system of the present disclosure may include at least one in-vehicle computer, and may include two or more in-vehicle computers. The in-vehicle computer and the in-vehicle network cable of the present disclosure may be directly or indirectly connected. For example, the in-vehicle network cable of the present disclosure and the in-vehicle computer may be connected via a hub, a router, or the like. The above-mentioned on-board computer is not limited as long as it is a computer mounted on a vehicle, and examples thereof include an on-board electronic control unit (on-board ECU) and an on-board telematic control unit (on-board TCU). The vehicle-mounted network system of the present disclosure may include a first vehicle-mounted computer, a second vehicle-mounted computer, and the vehicle-mounted network cable of the present disclosure that connects the first vehicle-mounted computer and the second vehicle-mounted computer. EXAMPLES

[0124] The present disclosure will now be described in detail with reference to examples. In the following examples, unless otherwise specified, "parts" and "%" represent "parts by mass" and "% by mass", respectively.

[0125] Production Example 1 Preparation of Pellet A Pellet A was obtained by the same method as that described in Example 1 of JP 2017-128119 A. The composition of the obtained pellet was a TFE / HFP / PPVE copolymer, TFE / HFP / PPVE=87.8 / 11.2 / 1.0 (mass ratio), melting point: 255°C, melt flow rate (MFR): 37g / 10min, and the total number of unstable terminal groups and -CF2H terminal groups was 1×10 carbon atoms. 6 The number was 0 per piece.

[0126] Production Example 3 Preparation of Pellet B Pellets obtained by the same method as that described in Synthesis Example 1 of WO2005-052015 were fluorinated to obtain pellets B. The composition of the obtained pellets was a TFE / PPVE copolymer, TFE / PPVE=94.9 / 5.1 (mass ratio), melting point: 255°C, melt flow rate (MFR): 63g / 10min, and the total number of unstable terminal groups and -CF2H terminal groups was 1×10 carbon atoms. 6 The number was 0 per piece.

[0127] Examples 1 to 5 and Comparative Examples 1 to 3 For the foamed electric wire molding, additives were added to the pellets obtained above, and the foam molding composition was adjusted by melt kneading to the specified amount, and then extruded with an extruder set to the extruder temperature shown in Table 1. A 22AWG copper wire (OD: 0.64mm) was used for the core wire, and the extrusion temperature, nitrogen gas introduction flow rate (pressure), extrusion speed, and take-up speed were adjusted so that the outer diameter after coating was 1.4mm, the wall thickness was 0.38mm, the skin was 25μm, and the electrostatic capacitance was 40pF / ft (corresponding to a foaming rate of 48%). The electric wire extrusion conditions are shown in Table 2. The experiment was continued for 1 hour, and spark outs were observed for 3,500 m of wire that had stabilized. The foaming rate, average aspect ratio, average bubble diameter, and surface roughness of the obtained foamed electric wire were measured by the following methods. The wire was also evaluated for crushing during twinning. The properties of the obtained electric wire were evaluated, and the results are shown in Tables 3 and 4.

[0128] [Table 1]

[0129] [Table 2]

[0130] The additives in Tables 3 and 4 are as follows. NA11 (ADEKA Corporation crystal nucleating agent ADK STAB NA-11): sodium 2,2'-methylenebis(4,6-di-t-butylphenyl) phosphate C4SBa salt: (C4F9SO3)2Ba Gelall MD (manufactured by New Japan Chemical Co., Ltd.): Bis(4-methylbenzylidene)sorbitol

[0131] Various properties in this specification were measured by the following methods. (Measurement of the number of unstable terminal groups) The pellets were rolled using a hydraulic press to produce a film with a thickness of about 0.3 mm, and the film was analyzed using an FT-IR Spectrometer 1760X (manufactured by Perkin-Elmer). A subtraction spectrum was obtained from a standard sample (a sample that had been sufficiently fluorinated to the point where no substantial difference was observed in the spectrum), and the absorbance of each peak was read and the carbon number (1 × 10) was calculated according to the following formula: 6 The number of unstable terminal groups per unit was calculated. Carbon number 1 x 10 6 Number of unstable terminal groups per unit = (I × K) / t (I: absorbance, K: correction factor, t: film thickness (unit: mm)) The correction coefficient (K) for each unstable terminal group is as follows: -COF(1884cm -1 )···405 -COOH(1813cm -1 , 1775cm -1 )···455 -COOCH3(1795cm -1 )···355 -CONH2(3438cm -1 )···480 -CH2OH(3648cm -1 )···2325

[0132] (Measurement of the number of -CF2H terminal groups) A nuclear magnetic resonance spectrometer AC300 (manufactured by Bruker-Biospin) was used, and the measurement temperature was set to (melting point of fluororesin + 20) °C. 19 F-NMR measurement was performed, and the integral value of the peak due to the presence of -CF2H groups and the integral values ​​of other peaks were used to determine the molecular weight.

[0133] (Melting Point) The melting point of the fluororesin was determined as the temperature corresponding to the peak when measured at a temperature rise rate of 10° C. / min using RDC220 (manufactured by Seiko Denshi Co., Ltd.).

[0134] (MFR) The MFR of the fluororesin was determined in accordance with ASTM D-1238 using a KAYENESS Melt Indexer Series 4000 (manufactured by Yasuda Seiki Co., Ltd.) with a die having a diameter of 2.1 mm and a length of 8 mm, at 372°C and a load of 5 kg.

[0135] (Outer diameter) The outer diameter of the electric wire was measured using a LASER MICRO DIAMETER LDM-303H-XY (manufactured by Takikawa Engineering Co., Ltd.).

[0136] (Capacitance) The capacitance was measured using a CAPAC300 19C (manufactured by Zumbach).

[0137] (number of sparks) The number of sparks per 3500m was measured using a Beta LaserMike Sparktester HFS1220 at a voltage of 1500V.

[0138] (Foaming rate) It was calculated as ((specific gravity of fluororesin - specific gravity of foam) / specific gravity of fluororesin) x 100.

[0139] (Average bubble diameter) An SEM image of the cross section of the wire perpendicular to the length direction was taken, and the diameter of each bubble was calculated by image processing. The average bubble diameter was calculated by averaging.

[0140] (Surface roughness) The surface of the electric wire was measured using a Keyence laser microscope, and the obtained image data was corrected by specifying the area of ​​the electric wire using quadratic curve correction for surface shape correction, and then the surface roughness of 500 x 2000 μm was calculated.

[0141] (Average aspect ratio of bubbles) An image of a cut surface parallel to the length of the coating material was taken using a scanning electron microscope (SEM), and the aspect ratio was measured by calculating the ratio of the long and short diameters (long diameter / short diameter) of each bubble obtained through image processing, and averaging the aspect ratios.

[0142] (Breakage of electric wires when twinned) The two electric wires were twisted together using an electric wire twisting machine under the following twisting conditions: The ratio of deformation to the initial diameter of the electric wire was defined as the deformation rate, and a deformation rate of 20% or less was deemed to be no crumbling. Linear speed: 19m / min Twisting: 3,000 twists / min Twist length: 8.5mm Deformation rate: (deformation from wire diameter / initial wire diameter) x 100 (%)

[0143] [Table 3]

[0144] [Table 4]

[0145] The foamed electric wire obtained in the examples did not suffer from crumbling during twinning and can be suitably used, particularly as an electric wire for an in-vehicle network cable. [Industrial Applicability]

[0146] The foam molding composition of the present disclosure is particularly suitable as a material for forming a covering material for a foamed electric wire.

Claims

1. A foam molding composition comprising a fluororesin (A) and a compound (B) having a thermal decomposition temperature of 300°C or higher and a solubility parameter (SP value) of 8 to 15, the composition being used for covering an electric wire for an in-vehicle network cable.

2. 2. The foam molding composition according to claim 1, wherein the compound (B) is a compound containing at least one partial structure selected from the group consisting of an aromatic ring, a phosphate ester group, and an amide group.

3. 3. The foam molding composition according to claim 2, wherein the compound (B) is a compound containing one or more C6-14 aromatic rings or a salt thereof.

4. 3. The foam molding composition according to claim 2, wherein compound (B) is at least one compound selected from the group consisting of phosphoric esters and their salts, phosphoric ester complex compounds, and compounds having two or more amide groups.

5. 5. The foam-molding composition according to claim 3, wherein the salt of compound (B) is an alkali metal or alkaline earth metal salt.

6. The foam-molding composition according to any one of claims 2 to 4, wherein compound (B) is at least one of compounds represented by the following formulas (1), (2), (3) and (4): 【Chemistry 1】 【Chemistry 2】 【Chemistry 3】 【Chemistry 4】 (In the formula, R 1 , R 2 , R 3 , R 4、 R 21 , R 22 , R 23 , R 24 , R 31 , R 32 , R 33 , R 34 , R 41 , R 42 represents a hydrogen atom, an alkyl group or a cycloalkyl group having 1 to 8 carbon atoms, or an aryl group, an alkylaryl group, or an arylalkyl group having 6 to 12 carbon atoms; Ar 41 represents an aryl group; R 5 , R 6 represents a hydrogen atom or a methyl group, n represents an integer of 1 or 2, m represents an integer of 0 to 2, and X represents a metal having a valence of m+n.

7. R in formula (1), formula (2), and formula (3) 1、 R 2、 R 21、 R 22、 R 31 and R 33 The foam molding composition according to claim 6, wherein is an alkyl group having 1 to 8 carbon atoms.

8. 7. The foam-molding composition according to claim 6, wherein X in formulas (1), (2) and (3) is at least one of sodium, potassium, rubidium, calcium and barium.

9. 7. The foam molding composition according to claim 6, wherein the compound (B) is an aromatic cyclic phosphate salt represented by the above formula (1).

10. 10. The foam-molding composition according to claim 9, wherein the compound (B) is sodium 2,2'-methylenebis(4,6-di-t-butylphenyl)phosphate.

11. The foam molding composition according to any one of claims 1 to 4, wherein the fluororesin (A) is a melt-processable fluororesin.

12. The foam molding composition according to any one of claims 1 to 4, wherein the fluororesin (A) is at least one selected from the group consisting of tetrafluoroethylene / hexafluoropropylene-based copolymers, tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers, and tetrafluoroethylene / ethylene-based copolymers.

13. 5. The foam-molding composition according to claim 1, wherein the fluororesin (A) is a fluororesin that has been fluorination-treated.

14. The foam-molding composition according to any one of claims 1 to 4, which is substantially free of a fluorine-based low molecular weight compound.

15. A foam-molded article obtained from the foam-molding composition according to any one of claims 1 to 4.

16. The foamed molded article according to claim 15, which is substantially free of a fluorine-based low molecular weight compound.

17. 5. A foamed electric wire for an in-vehicle network cable, comprising: a core wire; and a covering material obtained from the foam molding composition according to claim 1 and covering the core wire.

18. 18. The foamed electric wire for an in-vehicle network cable according to claim 17, which is substantially free of a fluorine-based low molecular weight compound.

19. A core wire and a fluororesin layer or a fluororesin composition layer coated on the core wire, The fluororesin layer or the fluororesin composition layer is a foamed electric wire having bubbles, A foamed electric wire for an in-vehicle network cable, characterized in that, when observed through a cross section perpendicular to the length direction, the average bubble diameter of the bubbles is 20 to 40 μm.

20. A core wire and a fluororesin layer or a fluororesin composition layer coated on the core wire, The fluororesin layer or the fluororesin composition layer is a foamed electric wire having bubbles, When observing a cut surface parallel to the length direction, A foamed electric wire for an in-vehicle network cable, characterized in that the average aspect ratio of the bubbles is 1.9 or less.

21. A core wire and a fluororesin layer or a fluororesin composition layer coated on the core wire, The fluororesin layer or the fluororesin composition layer is a foamed electric wire having bubbles, When observing a cut surface parallel to the length direction, A foamed electric wire for an in-vehicle network cable, characterized in that the proportion of bubbles having an aspect ratio of 3 or more is 13% or less of the total amount of bubbles measured by observation of a cut surface parallel to the longitudinal direction.

22. A core wire and a fluororesin layer or a fluororesin composition layer coated on the core wire, The fluororesin layer or the fluororesin composition layer is a foamed electric wire having bubbles, When observing a cut surface parallel to the length direction, A foamed electric wire for an in-vehicle network cable, characterized in that the standard deviation of the aspect ratio of the bubbles is 1.3 or less.

23. A core wire and a fluororesin layer or a fluororesin composition layer coated on the core wire, The fluororesin layer or the fluororesin composition layer is a foamed electric wire having bubbles, A foamed electric wire for an in-vehicle network cable, characterized in that the foaming rate is 20% or more and the surface roughness is less than 5.0 μm.

24. A core wire and a fluororesin layer or a fluororesin composition layer coated on the core wire, The fluororesin layer or the fluororesin composition layer is a foamed electric wire having bubbles, A foamed electric wire for in-vehicle network cables, characterized in that the electric wire has a foam (inner) / skin (outer) structure.

25. A method for producing a foam-molded article, comprising the step of foam-molding the foam-molding composition according to any one of claims 1 to 4.

26. A method for producing an electric wire, comprising the step of covering a core wire with the foam molding composition according to any one of claims 1 to 4 to obtain an electric wire.

27. An in-vehicle network cable comprising the foamed electric wire for an in-vehicle network cable according to any one of claims 17 to 24.

28. The vehicle-mounted network cable according to claim 27, comprising a twisted pair cable having a pair of electric wires twisted together, at least one of the pair of electric wires being a foamed electric wire for a vehicle-mounted network cable according to any one of claims 17 to 24.

29. 29. The vehicle-mounted network cable according to claim 28, wherein in the twisted pair cable, the deformation rate of the foamed electric wires after twisting is 20% or less.

Citation Information

Patent Citations

  • Shield twisted-pair cable

    JP2008287948A

  • Electric wire for onboard network cable and onboard network cable

    JP2021158111A

  • Foam molding composition, foamed molded body, electric wire, method for manufacturing foamed molded body, and method for manufacturing electric wire

    JP2022028640A